2015 IEEE International Conference on Robotics and Automation (ICRA) 2015
DOI: 10.1109/icra.2015.7139926
|View full text |Cite
|
Sign up to set email alerts
|

Using vanishing points to improve visual-inertial odometry

Abstract: This work presents a method for increasing the accuracy of standard visual inertial odometry (VIO) by effectively removing the angular drift that naturally occurs in feature-based VIO. In order to eliminate such drift, we propose to leverage the predominance of parallel lines in man-made environments by using the intersection of their image projections, known as vanishing points (VPs). First, an efficient inertial-based method is presented that accurately and efficiently detects such points. Second, a strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The vanishing points from parallel lines on the images relates to the camera orientation directly. It has shown that using vanishing points can improve visual SLAM [20] [21] and visual-inertial odometry [22]. However, in those methods the line features are used as only intermediate results for extracting vanishing points.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The vanishing points from parallel lines on the images relates to the camera orientation directly. It has shown that using vanishing points can improve visual SLAM [20] [21] and visual-inertial odometry [22]. However, in those methods the line features are used as only intermediate results for extracting vanishing points.…”
Section: Related Workmentioning
confidence: 99%
“…The process however becomes much simpler if an IMU is available, since the accelerometer renders the vertical direction observable because of gravity. We adopt a similar approach [22] to detect new Manhattan worlds in the image. We start Manhattan world detection whenever vertical lines have been identified as described in Section V-B.…”
Section: F Detecting and Merging Manhattan Worldsmentioning
confidence: 99%
“…A group of parallel lines project to image plane will converge to a vanishing point (VP). For example, Camposeco et al [20] deal VP as a measurement within an EKF-based visual-inertial odometry (VIO) system to improve the localization accuracy. Reference [21] use VP as a high-level landmark in a multilayer feature graph to directly calculate line landmarks direction in 3D space.…”
Section: A Line Segment Based Slammentioning
confidence: 99%
“…Two VPs of different groups of parallel lines can be used to estimate camera rotation [44]. VP has also been used for relative pose estimation [45] and as a measurement within an EKF-based visual-inertial odometry (VIO) system [20]. In [21], VPs are used as high-level landmarks in a multilayer feature graph, and the direction of such landmarks are represented by corresponding VPs.…”
Section: Geometry For Line Segments and Vanishing Pointsmentioning
confidence: 99%
“…An alternative method using only two dominant directions is presented by [ 16 ] based on the Rodrigues’ formula. The vanishing point-based attitude estimation method has been investigated to help indoor pedestrian navigation or improve VO performance in hallway environments [ 17 , 18 , 19 ] and UAV navigation in urban areas with structured buildings [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%